REAKTUALISASI PEMIKIRAN QADARIYAH DAN JABARIYAH TENTANG ILAHIYYAH DI ZAMAN DIGITAL - Fadlan Kamali Batubara; Rafly Ahmad; Lola Sischa Savilta; ⁠Yafizham Situmorang; ⁠Fadilah Sari; ⁠ ⁠Robiatul Adawiyah (STKIP Subang, 2026)
The development of the digital era has brought significant changes to the way people understand, disseminate, and reconstruct religious thought. In this context, the concept of ilahiyyah in classical Islamic theology, particularly within the Qadariyah and Jabariyah schools of thought, has regained scholarly attention due to its relevance to issues of human freedom, divine will, and moral responsibility amid technological advancement. This study aims to analyze the reactualization of the concept of ilahiyyah in Qadariyah and Jabariyah thought in the digital era and to examine its relevance to the challenges of modern life.This research employs a qualitative method with a library research approach through the examination of various sources discussing Islamic theology, the development of Qadariyah and Jabariyah thought, and the dynamics of digital society. The findings indicate that the concept of human freedom advocated by Qadariyah is relevant to fostering individual responsibility in the use of technology and information, while the concept of divine determination emphasized by Jabariyah provides a perspective on human limitations in the face of increasingly complex digital developments. The reactualization of these two theological perspectives is necessary to establish a balance between freedom, responsibility, and spiritual awareness, thereby ensuring that ilahiyyah values continue to serve as guiding principles in navigating digital transformation. Therefore, classical theological thought possesses not only historical significance but also the potential to contribute to a contextual understanding of religion in the digital age.